Medication Adherence in Type 2 Diabetes Mellitus Patients with Diabetic Ulcer: Systematic Literature Review: English - Safira Raissa Dwi Putri; Sony Wibisono Mudjanarko; Bambang Hermanto (Konsorsium Ilmu Biomedik Indonesia (KIBI), 2021)
Background: Patient non-adherence to diabetes medication can worsen the patient's condition and increase the risk of diabetes complications such as diabetic ulcers. A sufficient level of medication adherence can prevent diabetic complications. This study aimed to determine the level of medication adherence of type 2 DM patients with diabetic ulcers. Review: This research uses a systematic literature review with a PRISMA chart as a research design guideline. Researchers searched three databases, namely PubMed, Google Scholar, and ScienceDirect, using predefined keywords. The search resulted in 2,763 literatures then 11 literatures that met the criteria were taken. The number of respondents obtained amounted to 1,082 people. Characteristics of type 2 DM patients with diabetic ulcers: respondents were female, aged under 60 years, had diabetes for more than five years, used oral medication, insulin, or combination, could have normal or excess BMI, and possibly had hypertension or neuropathy. The result from systematic literature review obtained seven pieces of literature that had a low medication adherence level, two pieces of literature showed no correlation between medication adherence and the incidence of diabetic ulcers in type 2 DM patients, and two pieces of literature had a sufficient level of medication adherence. Summary: The level of medication adherence in type 2 DM patients with diabetic ulcers varies. However, more literature contains results in low medication adherence of type 2 Diabetes Mellitus patients with diabetic ulcers, so it needs to be improved in the future. Keywords: diabetic ulcer, medication adherence, type 2 diabetes mellitus